Code-Switching in Bilingual Classrooms - Uzoqova Marjona Sherali qizi (Journal of Innovation in Education and Social Research, 2025)
This paper explores the use of code-switching in bilingual classrooms, its pedagogical functions, sociolinguistic functions, and its impact on language acquisition. Code-switching, or the alternation of two or more languages within a conversation or a sentence, is a common phenomenon among bilingual speakers, particularly in classrooms where both learners and educators have more than one language in common. On the basis of data collected through observations of classes, teacher interviews, and student questionnaires, the study reveals the myriad functions of code-switching, such as clarification, emphasis, classroom management, and identity. The research illustrates how purposeful use of code-switching can aid student understanding, promote inclusivity, and connect home and school languages. However, the possible excessive use of the native language at the expense of immersion in the target language is also a point of concern. The findings suggest that code-switching, when employed purposively and not excessively, is an effective tool in bilingual education. The study contributes to what is known about language practice in multilingual classrooms and provides teaching staff with practical recommendations on how to reconcile code-switching with target language exposure.